2013
DOI: 10.1590/s1984-82502013000400015
|View full text |Cite
|
Sign up to set email alerts
|

A fully validated microbiological assay to evaluate the potency of ceftriaxone sodium

Abstract: Ceftriaxone (CFTX) sodium is a third-generation, broad-spectrum cephalosporin that is resistant to betalactamases. An alternative bioassay for the assessment of the potency of this drug in pharmaceutical formulations has not been previously reported. Thus, this paper reports the development and full validation of a 3 x 3 agar diffusion bioassay using a cylinder-plate method to quantify CFTX sodium in pharmaceutical samples. The strain Staphylococcus aureus ATCC 6538P was used as the test microorganism, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The microbiological assay employed in the present study to measure the concentrations of ciprofloxacin in plasma, was also used previously by many authors to measure the concentrations of fluoroquinolones including ciprofloxacin in the plasma/serum of animals (Haritova et al, 2006;Akhtar et al, 2007;Raina et al, 2008;Muhammad and Muhammad, 2009). It was found that bioassay method correlates well with HPLC studies (Zuluaga et al, 2009, Abdelaziz et al, 2011, Manfio et al, 2013.…”
Section: Pharmacokinetic Analysismentioning
confidence: 84%
“…The microbiological assay employed in the present study to measure the concentrations of ciprofloxacin in plasma, was also used previously by many authors to measure the concentrations of fluoroquinolones including ciprofloxacin in the plasma/serum of animals (Haritova et al, 2006;Akhtar et al, 2007;Raina et al, 2008;Muhammad and Muhammad, 2009). It was found that bioassay method correlates well with HPLC studies (Zuluaga et al, 2009, Abdelaziz et al, 2011, Manfio et al, 2013.…”
Section: Pharmacokinetic Analysismentioning
confidence: 84%
“…Biotransformation of antibiotics by resistant isolates under optimum culture conditions with time was evaluated by a microbiological assay (62). For this purpose, fractions of culture medium (2ml) were collected during growth curve analysis at different time intervals (3, 24, and 96 h).…”
Section: Determination Of Biotransformation Of Antibioticsmentioning
confidence: 99%
“…[2][3][4][5] Ceftriaxone sodium is a third-generation semi-synthetic cephalosporin, derived from a fermentation product, for parenteral use, being this group of extreme importance because they are able to overcome the blood-brain barrier, since previous generations do not have this capacity. [1,6,7] It acts on Gram-positive and Gram-negative bacteria, the activity against Gram-positive is noticeably smaller in relation to the first-generation cephalosporins. Its major activity is related to Gram-negative bacteria, and it is also capable of acting against Gram-negative bacilli resistant to the firstand second-generation cephalosporins.…”
Section: Introductionmentioning
confidence: 99%
“…Its major activity is related to Gram-negative bacteria, and it is also capable of acting against Gram-negative bacilli resistant to the firstand second-generation cephalosporins. [2,7,8,9] Ceftriaxone is presented in the form of single-ingredient preparations in the USA, United Kingdom, Japan and Canada as Rocephin TM ; in Brazil as Rocefin TM , Ceftriax TM , Celltriaxon TM , Keftron TM , Triaxin TM , Amplospec TM , Ceftriona TM , Triaxton TM ; in China as Ansailong TM , Cefin TM , Dezhi TM , Likang Kesong TM , Livzonphin TM , Locekin TM , Oframax TM , Rocephin TM , Xianqin TM ; in Germany as Cefotrix TM , Rocephin TM ; in Italy as Axobat TM , Bixon TM , Cefrag TM , Davixon TM , Daytrix TM , Deixim TM , Diaxone TM , Eftry TM , Eraxitron TM , Fidato TM , Frieng TM , Kocefan TM , Monoxar TM , Nilson TM , Panatrix TM , Pantoxon TM , Ragex TM , Rocefin TM , Setriox TM , Sirtap TM , Valexime TM . [10][11][12] It is indicated for cases of septicemia, meningitis, disseminated Lyme borreliosis (early and late stages of the disease) (Lyme disease), intra-abdominal infections (peritonitis, gastrointestinal and biliary tract infections), bone, joint, soft tissue, skin and wound infections, infections in immunocompromised patients, kidney and urinary tract infections; infections of the respiratory tract, particularly pneumonia andotolaryngological infections, genital infections, including gonorrhea, perioperative prophylaxis of infections.…”
Section: Introductionmentioning
confidence: 99%